2013
DOI: 10.1038/nature12799
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacteria manipulate macrophage recruitment through coordinated use of membrane lipids

Abstract: The evolutionary survival of Mycobacterium tuberculosis, the cause of human tuberculosis (TB), depends on its ability to invade the host, replicate, and transmit infection. At its initial peripheral infection site in the distal lung airways, M. tuberculosis infects macrophages which transport it to deeper tissues1. How mycobacteria survive in these broadly microbicidal cells is an important question. Here we show that M. tuberculosis, and its close pathogenic relative Mycobacterium marinum, preferentially recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
525
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 414 publications
(558 citation statements)
references
References 38 publications
13
525
2
Order By: Relevance
“…Studies performed in zebrafish model showed that the environment induced by mycobacterial infection stimulates the recruitment of highly motile macrophages in a matrix metalloproteases (MMP)-dependent manner, which is known to enhance the pathogenesis [43,44]. On the basis of these observations, we investigated whether cmMTB influences human monocyte-macrophages migration in different 3D environments that mimic tissues [45].…”
Section: The Cd16 + Cd163 + Mertk + Pstat3 + Monocyte-macrophages Dismentioning
confidence: 99%
“…Studies performed in zebrafish model showed that the environment induced by mycobacterial infection stimulates the recruitment of highly motile macrophages in a matrix metalloproteases (MMP)-dependent manner, which is known to enhance the pathogenesis [43,44]. On the basis of these observations, we investigated whether cmMTB influences human monocyte-macrophages migration in different 3D environments that mimic tissues [45].…”
Section: The Cd16 + Cd163 + Mertk + Pstat3 + Monocyte-macrophages Dismentioning
confidence: 99%
“…Our data suggest that MAP changes its phenotype during the stages of intracellular infection, and that these changes involve the alteration of whole cell-and cell wall-associated lipids. These changes are pertinent, as MAP has an abundant reliance on its lipid-rich cell wall for virulence and survival (Bansal-Mutalik & Nikaido, 2014;Cambier et al, 2014;Ehrt & Schnappinger, 2007). The upregulated genes we identified in this study are involved in a number of lipid-related processes.…”
Section: Discussionmentioning
confidence: 94%
“…PI3P is essential for phagosomes to acquire lysosomal constituents; it is involved in the docking of rab effector proteins early endosomal autoantigen 1 (EEA1) and hepatocyte growth factor-regulated tyrosine kinase (HRS) substrate, which are important for phagosome maturation [89]. Disruption of sapM in MTB resulted in a highly attenuated strain with an impaired ability to grow in the THP-1 macrophages as well as in the guinea pig tissues [33].…”
Section: Phagosome Arrestingmentioning
confidence: 99%
“…PDIM and PLG are major virulence factors of mycobacteria. PDIM and PGL are molecules required for bacterial duplication during the acute phase [33]. PDIM is involved in mycobacterial resistance to detergents, and also is linked with the permeability and envelope solidity [34].…”
Section: Phthiocerol Dimycocerosate (Pdim) and Phenolic Glycolipids (mentioning
confidence: 99%
See 1 more Smart Citation